Interactive effects of multiple stressors vary with consumer interactions, stressor dynamics and magnitude. (27th April 2022) - Turschwell, Mischa P.; Connolly, Sean R.; Schäfer, Ralf B.; De Laender, Frederik; Campbell, Max D.; Mantyka‐Pringle, Chrystal; Jackson, Michelle C.; Kattwinkel, Mira; Sievers, Michael; Ashauer, Roman; Côté, Isabelle M.; Connolly, Rod M.; et al.
Abstract: Predicting the impacts of multiple stressors is important for informing ecosystem management but is impeded by a lack of a general framework for predicting whether stressors interact synergistically, additively or antagonistically. Here, we use process‐based models to study how interactions generalise across three levels of biological organisation (physiological, population and consumer‐resource) for a two‐stressor experiment on a seagrass model system. We found that the same underlying processes could result in synergistic, additive or antagonistic interactions, with interaction type depending on initial conditions, experiment duration, stressor dynamics and consumer presence. Our results help explain why meta‐analyses of multiple stressor experimental results have struggled to identify predictors of consistently non‐additive interactions in the natural environment. Experiments run over extended temporal scales, with treatments across gradients of stressor magnitude, are needed to identify the processes that underpin how stressors interact and provide useful predictions to management. Abstract : Here, we use process‐based models to study how interactions generalise across three levels of biological organisation (physiological, population and consumer‐resource) for a two‐stressor experiment on a seagrass model system. We found that the same underlying processes could result in synergistic, additive or antagonistic inter‐actions, with interaction type depending on initial conditions, experiment duration, stressor dynamics and consumer presence